China’s Hegemonic Trajectory: Intimidating ASEAN? - Mushahid Ali (2016)
Fierce criticism of Singapore by China’s spokespersons for allegedly stirring up tension over the South China Sea at international forums reflects a pattern of interference in ASEAN’s deliberations; this suggests that Beijing is embarked on a hegemonic trajectory in Asia.